Diabetes Induces p66shc Gene Expression in Human Peripheral Blood Mononuclear Cells: Relationship to Oxidative Stress - Pagnin, Elisa; Fadini, Gianpaolo; de Toni, Renzo; Tiengo, Antonio; Calò, Lorenzo; Avogaro, Angelo (The journal of clinical endocrinology and metabolism, 2005)
Oxidative stress plays a role in cardiovascular dysfunction. This is of interest in diabetes, a clinical condition characterized by oxidative stress and increased prevalence of cardiovascular disease. The role of p66shc in oxidative stress-related response has been demonstrated by resistance to and reduction of oxidative stress and prolonged lifespan in p66shc−/− mice. In this study we assess p66shc gene expression in peripheral blood mononuclear cells (PBM) from type 2 diabetic patients and healthy subjects. The p66shc mRNA level was assessed using RT-PCR with two sets of primers mapping for different p66shc regions. p66shc is expressed in both monocytes and lymphocytes. The level of p66shc mRNA was significantly higher in type 2 diabetic patients compared with controls (0.38 ± 0.07 densitometric units vs. 0.13 ± 0.08; P < 0.0001). In addition, total plasma 8-isoprostane levels, a marker of oxidative stress, were higher in type 2 diabetics (0.72 ± 0.04 ng/ml) than in normal subjects (0.43 ± 0.04, P < 0.001) and were significantly correlated to the p66shc mRNA level in PBM from type 2 diabetics (r2 = 0.47; P = 0.0284). In conclusion, diabetes induces p66shc gene expression in circulating PBM; this up-regulation in expression is significantly associated with markers of oxidative stress. p66shc gene expression in PBM may represent a useful tool to investigate the oxidative stress involved in the pathogenesis of long-term diabetic complications.